2014
DOI: 10.4028/www.scientific.net/amr.906.159
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Activated Carbon Using Photo-Oxidation Process

Abstract: Activated carbon has been used as an adsorbent for centuries. For purpose of regeneration, advanced oxidation processes is sugested, this approcah could be viable from the econmic and environmental point of view, and appears as an alternative to the many of inefficient single-step processes actaully applied for the regeneration process. The results showed that the Titanium dioxide can easily regenerate the AC by oxidizing the organic compounds adsorbed on the surface of AC. The increase of UV light intensity h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…He concluded only 20 ppm of phenol was removed. Al-Dawery [29] demonstrated that the ability of TiO 2 for regeneration of AC increased by increasing the intensity of UV light.…”
Section: Desalination and Water Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…He concluded only 20 ppm of phenol was removed. Al-Dawery [29] demonstrated that the ability of TiO 2 for regeneration of AC increased by increasing the intensity of UV light.…”
Section: Desalination and Water Treatmentmentioning
confidence: 98%
“…
To cite this article: Salam K. Al-Dawery (2014): Adsorption of methanol from methanol-water mixture by activated carbon and its regeneration using photo-oxidation process, Desalination and Water Treatment, Activated carbon (AC) has been used as an adsorbent for centuries as a result of its ability to remove a large variety of compounds from contaminated waters. The objective of this study was to investigate the removal of methanol by adsorption and the use of advanced oxidation process for the regeneration of the exhausted AC as an alternative to thermal, biological, and chemical methods that are currently applied.
…”
mentioning
confidence: 99%
“…[ 139 ] The PCO process, which promotes the breakdown of organic substances when exposed to UV radiation, is another means of regeneration. [ 140 ] Satter et al [ 141 ] used heat treatment of the spent catalyst in a He flow and regenerated the original activity for subsequent reaction. Another group of investigators demonstrated the use continuous adsorption and electrochemical regeneration using an air‐lift reactor.…”
Section: Strategies For Improving Photocatalytic Efficiency Aiming At...mentioning
confidence: 99%